Eksplorasi dan Identifikasi Mikroba Rhizosfer Bawang Merah (Allium ascalonicum L.) yang Diaplikasi Pestisida Nabati di Lahan Gambut Landasan Ulin Kalimantan Selatan - Elvina Royani Maliq; Salamiah Salamiah; Yusriadi Marsuni (Universitas Lambung Mangkurat, 2020)
Shallot (Allium ascalonicum L.) is one of horticultural plants which is widely used by humans. Onion growth and development are very affected by factors which become obstacles in the cultivation of onion plants. One of the factors that hinder the cultivation of shallot is disease infection that attacks the plants. The disease is caused by fungi, bacteria, viruses, and various other pathogens. It causes a decrease in crop productivity. One of the efforts to get rid of the diseases which attack shallots is using plant-based pesticides. This study aims to determine the various types and the level of diversity of rhizosphere microbial on onion plantations applied with plant-based pesticides on peatlands in South Kalimantan. This research was carried out in the village of Tegal Arum Landasan Ulin and in the Production Laboratory of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. This research uses descriptive method by taking samples in the onion planting field which are treated with plant-based pesticides. They are P0: Control Treatment, P1: 2.4 g Dithane M-45 fungicide L-1, P2: 1 ml chirinyu extract L -1, P3: 1 ml Kepayang extract L-1, P4: 1 ml Galam extract L-1. The results of identification in this study showed, there were 32 isolates. There were seven types of fungi and two types of bacteria found in the onion rhizosphere that had been applied with various types of plant-based pesticides and has a moderate level of diversity: plan treated by galam-based pesticides (H ′ = 1.75 ), kepayang-based (H ′ = 1.73), Dithane fungicide M-45 (H ′ = 1.15) and control (H ′ = 1.33), onion treated by chirinyuh - based pesticides (H ′ = 0.99) has low level of diversity due to chirinyuh extract has the potential as an antimicrobial.